The Design and Implementation of the Secretariat Website of the Tanjungbalai City Regional Representative Council: An Analysis within the Framework of Field Work Practice - Sinaga, Muhammad Nabil; Ramadhan, Nuzul (The Future of Education Journal, 2025)
In this research, the design and implementation of the website of the Regional People's Representative Council (DPRD) of Tanjungbalai City is used as an analysis in the framework of Field Work Practice (PKL). The main objective of this research is to improve the availability of information and communication between the DPRD of Tanjungbalai City and the community through a digital platform. The research method includes the interface design phase using HTML and CSS and the application of web technologies to create a responsive and functional DPRD website. Analyzing user requirements, user interface design and integration of features that support transparency and audience. The results of this research are expected to increase the effectiveness of communication and public understanding of DPRD of Tanjungbalai City activities and strengthen DPRD's relationship with its constituents through the use of information technology.